Wastewater generation its scope in Indian agriculture - Rama, Pal; Dubey, R K; Dubey, S K (Indian Farming, 2019)
Despite water being an existential base for life, it is one of the most under prioritized and over abused commodities. With the increase in population, greater volumes of surface and groundwater are being diverted to supply burgeoning cities and concomitantly a substantial volume of urban wastewater is being produced. In order to fulfil food demand of growing population as well as the present scenario of water crisis, the farmers are inclining towards wastewater utilisation in agriculture. India is primarily an agriculture-based country and its economy largely depends upon agriculture. Therefore, the safe use of wastewater in agriculture is an important issue that needs to be addressed. National policies should be devised to provide guidelines and practices regarding safe use of wastewater in agriculture.